Demo: Using LoRa Communications and Epidemic Routing in Disaster Rescue Operations - Dalpathadu, Yamani; Thumma, Showry; Udugama, Asanga; Förster, Anna (Electronic Communications of the EASST, 2021)
A casualty of disasters is the communication infrastructure. Rescuers, in the aftermath of the disaster, require solutions to maintain communications in order to communicate critical information gathered by them. Despite the numerous solutions proposed, a drawback is the communication range. In this work, we propose a communication system based on LoRa, a long-range, low-power communication technology. We use the commercially available, off-the-shelf LoRa based PyCom LoPy4 platform with opportunistic networking to demonstrate the viability of using LoRa for post-disaster recovery operations.